Indocyanine green (ICG) angiography-guided thyroidectomy: description of surgical technique - Moreno-Llorente, Pablo; Pascua-Solé, Mireia; García-Barrasa, Arantxa; Muñoz-de-Nova, José Luis (Frontiers in Surgery, 2023)
Background: Postoperative hypoparathyroidism is the most common complication after total thyroidectomy and, when becomes permanent, lead to a myriad of clinical symptoms, long-term need of calcium and vitamin D supplementation and negative impact on the patient’s health-related quality of life. Any surgical innovation that could reduce complications and improve outcomes of patients undergoing total thyroidectomy deserves to be considered. Angiography-Guided Thyroidectomy has been proposed as a modification of the standard technique of thyroidectomy aimed to identifying the vascular pattern of the parathyroid glands to maximize efforts for preserving functioning glands at the time of operation. Our aim is to provide a technical description of this procedure based on the use of indocyanine green (ICG) angiography to standardize this technique. Methods: The surgical steps that are followed during a total thyroidectomy are modified due to previous visualization of the feeding vessels of the parathyroid glands according to fluorescence of the vascular mapping obtained by ICG angiography prior to thyroidectomy. The first step is to perform an ICG angiography to assess anatomical features of the feeding vasculature of the parathyroid glands, which allows precise surgical dissection for preservation of the glands. Once the viability of the parathyroids has been evaluated angiographically, thyroidectomy is performed in a second step. Conclusions: ICG angiography-guided thyroidectomy may be effective to preserve the largest number of better perfused parathyroid glands, which would contribute to reduce the risk of postoperative and permanent hypoparathyroidism. It can be successfully and safely implemented in thyroid surgery and standardization of the technique is necessary to homogenize this procedure in the future, allowing a better comparation of the results to be published.